TEACHING PATRIOTISM THROUGH THE METHODS OF REALIZING "COMMUNITY AND PERSONAL INTEREST" IN HIGHER EDUCATION - Khasanov Nurmukhammad Khaydarali ugli; Ubaydullayev Saidakbar Saydaliyevich; Alinazarov Nodirkhon Nosirkhonzoda (Galaxy International Interdisciplinary Research Journal, 2022)
In this article, from educating students in the spirit of patriotism to organizing the activities of social institutions, methods of educating young people in the spirit of patriotism, the use of educational centers for the defense of the motherland and military service Key words: patriotism, education, the younger generation, military service, Youth Union, decree, law , order, state.